Pregnancy-related Mortality in the United States, 2011 to 2013. Issue 1 (March 2018) - Creanga, A.A.; Syverson, C.; Seed, K.; Callaghan, W.M.
Abstract : ( Obstet Gynecol . 2017;130(2):366–373) A pregnancy-related death is defined as the death of a woman during or within 1 year ofpregnancy that was caused by a pregnancy complication, a chain of events initiated by pregnancy, or the aggravation of an unrelated condition by the physiologic effects of pregnancy. In the United States, the pregnancy-related mortality ratio has increased from 10 deaths per 100, 000 live births in the 1990s to 16 deaths per 100, 000 live births in the aggregate period of 2006 to 2010. Reasons for this increase are not entirely clear. Therefore, in this observational study, the authors examined pregnancy-related mortality, causes of death, and populations at risk in the United States for the time period between 2011 and 2013.